Potential Role of Fungal Endophytes in Biological Nitrification Inhibition in Brachiaria Grass Species - Odokonyero, Kennedy; Acuña, Tina Botwright; Cardoso Arango, Juan Andrés; Jiménez Serna, Juan de la Cruz; Rao, Idupulapati M.; Nuñez, Jonathan; Arango, Jacobo (OMICS Publishing Group, 2017)
Brachiaria species have the ability to suppress nitrification in soil by releasing an inhibitory compound called ‘brachialactone’ from its roots; a process termed biological nitrification inhibition (BNI). This study tested the hypothesis that endophytic association with Brachiaria grass improves BNI activity of root tissues and reduces nitrification in Brachiaria-cultivated soil. Four cultivars of Brachiaria [i.e., B. decumbens (Basilisk), B. humidicola (Tully), B. brizantha (Marandu)], and one hybrid (Cayman) were evaluated for their BNI potentials under greenhouse and field conditions. In each experiment, plants were grown with (E+) and without (E-) endophyte inoculation, and harvested after eight months of growth. Root tissues and rhizosphere soil were taken from 0-30 cm depth and analyzed for BNI activity and nitrification, using bioluminescence assays and soil incubation, respectively. In the greenhouse experiment, endophyte association reduced BNI activity of root tissues in at least two cultivars (Basilisk and Marandu; by 13% and 6%, respectively); and this corresponded with 9% and 10% higher rates of nitrification (for Basilisk and Marandu, respectively) in soils grown with endophyte-infected plants than in the control. Under field conditions, endophyte association increased rates of nitrification in Marandu and Cayman by a similar magnitude of 12%, compared with endophyte-free control. In both experiments, Tully and Basilisk were essentially the most outstanding candidates for low-nitrifying forage systems, as shown by their high BNI activity and/or low rates of nitrification. The study also showed that cultivating soils with Brachiaria grasses could offer more agronomic and environmental benefits due to low N loss through nitrification than leaving the soils bare. However, further research to identify endophyte species that could suppress soil nitrifying microbes may enhance BNI process in Brachiaria.